Complex sexual-social environments produce high boldness and low aggression behavioral syndromes - Queller, Philip S.; Shirali, Yasmin; Wallace, Kelly J.; DeAngelis, Ross S.; Yurt, Vural; Reding, Luke P.; Cummings, Molly E. (Frontiers in Ecology and Evolution, 2022)
Evidence of animal personality and behavioral syndromes is widespread across animals, yet the development of these traits remains poorly understood. Previous research has shown that exposure to predators, heterospecifics, and urbanized environments can influence personality and behavioral syndromes. Yet, to date, the influence of early social experiences with conspecifics on the development of adult behavioral traits is far less known. We use swordtail fish (Xiphophorus nigrensis), a species with three genetically-determined male mating strategies (courtship display, coercion, or mixed strategy) to assess how different early-life social experiences shape adult behavioral development. We raised female swordtails from birth to adulthood in density-controlled sexual-social treatments that varied in the presence of the type of male mating tactics (coercers only, displayers only, coercers and displayers, and mixed-strategists only). At adulthood, we tested females’ boldness, shyness, aggression, sociality, and activity. We found that the number of different mating strategies females were raised with (social complexity) shaped behavioral development more than any individual mating strategy. Females reared in complex environments with two male mating tactics were bolder, less shy, and less aggressive than females reared with a single male mating tactic (either courtship only or coercion only). Complex sexual-social environments produced females with behavioral syndromes (correlations between aggression and activity, shyness and aggression, and social interaction and activity), whereas simple environments did not. Importantly, the characteristics of these socially-induced behavioral syndromes differ from those driven by predation, but converge on characteristics emerging from animals found in urban environments. Our findings suggest that complexity of the sexual-social environment shapes the development of personality and behavioral syndromes to facilitate social information gathering. Furthermore, our research highlights the previously overlooked influence of sexual selection as a significant contributing factor to diverse behavioral development.